2013
DOI: 10.1007/s00405-013-2432-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct round window stimulation with the Med-El Vibrant Soundbridge: 5 years of experience using a technique without interposed fascia

Abstract: The objective of this study was to present 5 years of surgical experience, and the extended results of hearing preservation (based on 3-year follow-up), with the Med-El Vibrant Soundbridge (VSB) in which the floating mass transducer (FMT) is placed directly against the round window membrane, and the fascia is used only as covering tissue to keep it in position. A retrospective survey of surgical and audiological data was conducted to evaluate the performance and stability of patient hearing, with audiometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 5 publications
4
31
0
8
Order By: Relevance
“…Schraven et al [2016] report on high revision surgery numbers of up to 71% in RW vibroplasty without coupler usage. We observed a revision surgery rate of 11% in the RW coupler group (1/9) which is in agreement with previous works [Skarzynski et al, 2014;Zhao et al, 2016]. Although an ossicular attachment point for the FMT is surgically less challenging than RW vibroplasty which requires drilling of the RW niche, RW vibroplasty using the RW coupler is the best alternative for cases where no ossicular chain is present.…”
Section: Discussionsupporting
confidence: 80%
“…Schraven et al [2016] report on high revision surgery numbers of up to 71% in RW vibroplasty without coupler usage. We observed a revision surgery rate of 11% in the RW coupler group (1/9) which is in agreement with previous works [Skarzynski et al, 2014;Zhao et al, 2016]. Although an ossicular attachment point for the FMT is surgically less challenging than RW vibroplasty which requires drilling of the RW niche, RW vibroplasty using the RW coupler is the best alternative for cases where no ossicular chain is present.…”
Section: Discussionsupporting
confidence: 80%
“…Careful drilling to widen the RW niche is often required, which could be one drawback to this approach. In comparison with this technique [Colletti et al, 2013;Skarzynski et al, 2014], the RW coupler may improve vibroplasty by adding a more stable substance to the fascia or cartilage (or eliminating the need for it), while also reducing the amount of drilling at the RW niche [Lüers and Hütten-brink, 2014]. Schwab et al [2013] state that using the RW coupler is a safer and more effective surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature [Böheim et al, 2012;Skarzynski et al, 2014], audiometric thresholds have been reported to be stable 12 months postoperatively, with aided performance significantly improved over preoperative measurements. Additionally, basic audiological tests showed that the air and BC thresholds of the patients were not altered by the operation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stability of the FMT in the round window niche may be maintained by bracing the FMT to the hypotympanum (17). However, Skarzynski et al (18) reported no significant difference in bone conduction thresholds after 36 months when placing the FMT directly on the round window and only using fascia to cover the FMT. In this cohort, three subjects (S3, S7, and S9) required revision surgery during the study period due to displacement of the FMT from the round window niche.…”
Section: Discussionmentioning
confidence: 97%